Large‐Scale Synthesis of Nitrogen‐Doped Activated Carbon Fibers with High Specific Surface Area for High‐Performance Supercapacitors. Issue 5 (6th March 2020) - Liao, Ming Dong; Peng, Chuan; Hou, Sheng Ping; Chen, Jian; Zeng, Xian Guang; Wang, Hao-Lun; Lin, Jarrn-Horng
Abstract : Activated carbon nanofibers (ACFs) with high specific surface area, excellent conductivity, and narrow pore‐size distribution, are regarded as a promising electrode material for high‐performance supercapacitors (SCs). Herein, a facile route to synthesize large‐scale amorphous CF (a‐CF) using catalytic pyrolysis of acetylene (C2 H2 ) at 260 °C over copper catalysts is reported. The conversion rate of acetylene into a‐CF is estimated as high as 72.05 wt%. Subsequently, the as‐prepared a‐CF is transformed into ACFs by potassium hydroxide (KOH) at 800 °C with high specific surface area and porous structures. Moreover, nitrogen‐doped ACFs are conducted in the activation step through a physical mixing of a‐CF/KOH/melamine with various ratios. For SCs, the as‐prepared N‐ACFs display excellent specific capacitance and cycle stability. In the three‐electrode system, the N‐ACF (CF‐03) demonstrates a specific capacitance value of 227 F g −1 at 0.5 A g −1, and shows a 94% capacitance retention after a long cycle (10 000 cycles) at 2 A g −1 . Moreover, the CF‐03‐based two‐electrode SC demonstrates a high energy density of 14.30 Wh kg −1 and a high power density of 79.88 W kg −1 in 1 m Na2 SO4 electrolyte. Herein, a simple and promising way to prepare large‐scale a‐CF, ACF, and N‐doped ACFs is demonstrated. Abstract : Nitrogen‐doped activated carbon nanofibers (N‐ACF) demonstrate excellent electrochemical performance with a specific capacitance value of 227 F g −1 at 0.5 A g −1, and show a 94% capacitance retention after 10 000 cycles at 2 A g −1 . Moreover, N‐ACF‐based electrode displays a high energy density of 14.30 Wh kg −1 and a high power density of 79.88 W kg −1 .